Analisis Sejarah Kelembagaan Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) Al-Muttaqin, Kabupaten Deli Serdang - Hafidoh Hafidoh (-, 2021)
The purpose of this study was to determine the institutional history of Madrasah Diniyah Takmiliyah Awaliyah, by taking the research location at MDTA Al-Muttaqin which is located at Jl. Karya III, Hamlet II, Helvetia, Sunggal District, Deli Serdang Regency. MDTA Al-Muttaqin, which is under the auspices of the Al-Muttaqin Mosque's National Authority, obtained an operating permit from the Ministry of Religious Affairs, Kab. Deli Serdang. This study uses a qualitative method with a descriptive approach. Collecting data using the method of observation, interviews and documentation. The data analysis technique used a descriptive approach. The object of research is the history of the development of MDTA Al-Muttaqin. The results of the study discuss the history of Al-Muttaqin MDTA, along with a discussion of relevant previous research studies.